Molecular characterization of tick-borne bacterial and protozoan pathogens in parasitic ticks from Xinjiang, China - Bingjie Wang; Zhiqiang Liu; Shiying Zhu; Jinchao Zhang; Wenwen Qi; Jianyu Wang; Dongfang Li; Lan He; Junlong Zhao (Parasites & Vectors)
Abstract Background Ticks are a type of hematophagous parasite, serving as critical vectors of pathogens that cause numerous human and animal diseases. Climate change has driven the geographical expansion of tick populations and increased the global transmission risk of tick-borne diseases. However, there has been a lack of comprehensive data on tick species distribution and their associated pathogen profiles in Xinjiang, China. Methods Ticks were collected from 19 sampling sites across nine regions in Xinjiang. The species were identified using both morphological and molecular biological methods. The presence of tick-borne bacterial and protozoan pathogens was detected through polymerase chain reaction (PCR). Finally, sequencing and phylogenetic analyses were performed to further characterize the identified ticks and pathogens. Results A total of 1093 ticks were collected and identified, representing four genera and nine species, with Hyalomma asiaticum being the dominant species. Haplotype diversity and genetic differentiation analysis based on the 16S rRNA gene of the dominant species demonstrated that the Hy. asiaticum population in Xinjiang exhibits high haplotype diversity (Hd = 0.734), low nucleotide diversity (π = 0.00403), and significant genetic differentiation (Fst = 0.19716). Pathogen detection using PCR revealed an infection rate of 9.3% for Anaplasma, 18.1% for Rickettsia, and 9.0% for piroplasms. Phylogenetic analysis based on 16S rRNA sequences indicated that the Anaplasma genus identified in ticks comprised Anaplasma ovis, Anaplasma sp., and Anaplasma phagocytophilum. Phylogenetic analysis based on the opmA gene showed that the Rickettsia genus identified in ticks included Rickettsia aeschlimannii, Rickettsia conorii, Rickettsia slovaca, Rickettsia conorii subsp. raoultii, Rickettsia sp., Candidatus Rickettsia barbariae, and Candidatus Rickettsia jingxinensis. Similarly, phylogenetic analysis based on the 18S rRNA gene demonstrated that the piroplasms identified in ticks included Theileria annulata, Theileria ovis, Babesia bigemina, Babesia occultans, and Babesia sp. All gene sequences of the detected pathogens showed 99.8–100% identity with corresponding sequences deposited in GenBank. Conclusions This study demonstrates that Xinjiang harbors a rich diversity of tick species with a wide geographical distribution. Furthermore, the tick-borne pathogens in this region are complex and diverse. These results underscore the necessity of sustained and enhanced surveillance efforts targeting ticks and tick-borne diseases in this region Graphical abstract